Association between the use of antibiotics and efficacy of gemcitabine plus nab-paclitaxel in advanced pancreatic cancer. Issue 39 (25th September 2020) - Nakano, Shintaro; Komatsu, Yoshito; Kawamoto, Yasuyuki; Saito, Rika; Ito, Ken; Nakatsumi, Hiroshi; Yuki, Satoshi; Sakamoto, Naoya
Abstract : Abstract: It is unclear whether the use of antibiotics is related to the efficacy of gemcitabine plus nab-paclitaxel (GnP). Therefore, we investigated the association between the use of antibiotics and efficacy of GnP. We conducted a retrospective single center study from January 2014 to December 2018 in Hokkaido University Hospital. Ninety-nine patients were eligible for the study. Thirty-seven used antibiotics (U) and 62 did not use antibiotics (NU) during GnP therapy. In the U group, 15 patients used β-lactam antibiotics, 21 used new quinolones, and 1 used carbapenem. The median progression-free survival was 5.8 and 2.7 months (hazards ratio [HR] .602, 95% confidence interval [CI] .391–.928, P  = .022) and the median overall survival was 11.0 and 8.4 months (HR .768, 95% CI .491–1.202, P  = .248) in the U and not use antibiotics groups, respectively. Antibiotic use (HR .489, 95% CI .287–.832, P  = .008) and locally advanced pancreatic cancer (HR 1.808, 95% CI 1.051–3.112, P  = .032) were independent prognostic factors for progression-free survival. Antibiotic use was associated with a higher efficacy of GnP, and therefore, it may be employed as a novel treatment strategy.